PROBLEMS OF EDUCATION AND UPBRINGING IN THE WORKS OF AL-FARABI - Zhazykova, R.B. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
The article discusses the views of the great son of the Kazakh steppe – Abu Nasr al-Farabi on the role and place of education and upbringing in the formation and development of mankind, the problems of science and education.
Keywords: upbringing; education; science; civilization; teacher; student; labor